REPRODUCTIVE PERFORMANCE OF SOWS IN RURAL COMMUNITIES OF ASSAM - AHMED, K; AHMED, N; KALITA, D (The Indian Journal of Animal Reproduction, 2016)
The reproductive performance of breeding sows in rural households of Districts Kamrup and Darrang, Assam was assessed through a survey of 300 farmers. Average number of sows owned by each household was 2.7±0.7, average litter size at farrowing was 7.2±2.8, sows were bred 2.3±1.08 month subsequent to weaning of piglets and breeding was done at 2.3±1.7 day after the onset of estrus. The source of breeding boar was neighbor’s household (86%), farmers’ own house (12%) and community owned boar (2%). In brief, there is need to encourage and educate sow farming community to maximize the opportunity for reproductive performance.
Keywords: Assam; Reproductive performance; Rural community; Sow; Survey